P-141 COVID-19, long-COVID and return-to-work a questionnaire to investigate the experience of the occupational physicians from an Italian region. (14th March 2023) - Modenese, Alberto; Gobba, Fabriziomaria
Abstract : Introduction: The issues related to return-to-work (RTW) after COVID-19, and the impact of long-COVID on workers' health engaged in different occupations are far to be fully acknowledged. Occupational Physicians (OPs) represent an important and competent source for the evaluation of these issues in workplaces, scant considered in research up now. Material And Methods: A literature search was performed to develop a questionnaire targeting the Italian OPs. The survey collects data on COVID-19 related RTW issues and on long-COVID symptoms occurrence in workers of Emilia-Romagna region (Italy). Results: The questionnaire involves three sections. The first with general information on the OPs activity (industrial sector and types of companies followed, main occupational hazards, health surveillance programs carried out). The second section is about long-COVID, defined according to the World Health Organization and the U.S. Centers for Disease Control and Prevention. A list of 22 symptoms based on a systematic search in MedLine has been developed asthenia; air hunger; chest tightness; memory/concentration problems; mental confusion; joint/muscle pain; sleep disorders; heart palpitations; dizziness; tingling/dysesthesia; gastrointestinal problems; depression and/or anxiety; tinnitus; inappetence; low-grade fever; high-grade fever; cough; headache; sore-throat; changes in smell/taste; skin rashes; other symptoms (to be specified). The main characteristics of the workers with long-COVID (age, gender, concomitant diseases, vaccination, smoking habit, body weight and previous infections etc.) and the frequency of the long-COVID symptoms are collected. The last section investigates RTW issues, to quantify the impact of the phenomenon in terms of workers involved, main characteristics of subjects with RTW problems, and implications for their work-ability. Conclusions: Using the OPs direct experience as source of information, the study is aimed to develop new knowledge on the long-term impacts of the SARS-CoV-2 pandemic on workers' health, specifically considering RTW issues and the occurrence of long-COVID symptoms.